Ontological services level agreement (SLA) model and its application in cloud computing environment. - Abdullah, Rusli (2013)
Service Level Agreement (SLA) is a contractual agreement that has been established between the members of community of practice (CoP) that consists of the service provider and the recipient for a specific application of services based on its allocating and sharing resources as a services in cloud computing. This agreement is an outcome that based on negotiation process will be identifying and describing the SLA that has been offered by the service provider or ownership of the cloud to their respective recipients. The resource allocation engagement or what we called as RaaS are including the software (Software as a Service - SaaS), infrastructure (Infrastructure as a Service – IaaS), and platform (Platform as a Service – PaaS). In this context, there are many parties who are very concerning about it, but unfortunately there is lacking of a common of SLA of best practice as a guideline that can be used for CoP to make use for the future purposes in engaging with services in the cloud environment. Therefore, in this paper will discuss the model of SLA in order to ensure everybody who are providing and receiving the services in the cloud satisfied and getting the best maximum return of the investment in allocating and sharing resources among the providers and recipients in cloud computing environment.